2023
DOI: 10.1038/s41467-023-37058-y
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase synthesis of the C40 nano bowl C40H10

Abstract: Nanobowls represent vital molecular building blocks of end-capped nanotubes and fullerenes detected in combustion systems and in deep space such as toward the planetary nebula TC-1, but their fundamental formation mechanisms have remained elusive. By merging molecular beam experiments with electronic structure calculations, we reveal a complex chain of reactions initiated through the gas-phase preparation of benzocorannulene (C24H12) via ring annulation of the corannulenyl radical (C20H9•) by vinylacetylene (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The exploitation of PIE curves and ms-TPE spectra in tandem enables isomer-selective identification of hydrocarbon molecules (Supporting Information, Figures S7 and S8). …”
Section: Resultsmentioning
confidence: 99%
“…The exploitation of PIE curves and ms-TPE spectra in tandem enables isomer-selective identification of hydrocarbon molecules (Supporting Information, Figures S7 and S8). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Tuli et al 412 suggested a new "bottom-up" pathway to form a building block of fullerenes�a nanobowl C 40 H 10 . The nanobowl can be obtained through a chain of reactions starting from the corannulene molecule, whose formation was described above in Section 5.2.3.…”
Section: Formation Of Carbon Nanoparticles and Grainsmentioning
confidence: 99%
“…Additionally, several efforts on synthesis and characterization were done focused on C 60 H 2 and C 60 H 4 fulleranes. 24–30 Furthermore, a recent successful and facile bottom-up synthesis of C 40 H 10 from benzocorannulene, a structural isomer of coronene, 31 further emphasizes the significance of fulleranes in the astrochemical context.…”
Section: Introductionmentioning
confidence: 99%